2013
DOI: 10.1108/sajgbr-05-2011-0010
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth and energy consumption nexus in Pakistan

Abstract: PurposeThis study aims to examine the relationship between electricity consumption per capita (ELEC) and real per capita income (Y), as the direction of causation of this relationship remains controversial in the existing literature. It also seeks to explore the relationship between energy consumption per capita (ENC) and real per capita income, over a 34‐year period (between 1975 and 2009).Design/methodology/approachThe study uses Johansen cointegration technique to determine the short‐ and long‐run relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The study of Joyeux and Ripple [31] shows causality runs from income to energy consumption for 56 developed and developing countries. Ahmed et al [2] provide evidence of bi-directional causality between the per capita electricity consumption and real per capita income in Pakistan during 1975-2009.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…The study of Joyeux and Ripple [31] shows causality runs from income to energy consumption for 56 developed and developing countries. Ahmed et al [2] provide evidence of bi-directional causality between the per capita electricity consumption and real per capita income in Pakistan during 1975-2009.…”
Section: Literature Reviewmentioning
confidence: 97%
“…The study of Grossman and Krueger[25] has shown that with the advanced stage of economic development, the high-polluting industrial economy turns into service economy or technology-based economy with the changes in the economic structure of the country, where the degree of environmental pollution is turn down 2. According to the United Nations Environment Programme (2011: 16) green economy as an economy that leads to "improved human well-being and social equity, while significantly reducing environmental risks and ecological scarcities".…”
mentioning
confidence: 99%
“…For example, Li [27] found that China's energy consumption has a significant positive effect on economic growth and the eastern region of China has the most effective effect. Ahmed et al [28] investigated the relationship between per capita electricity consumption and per capita real income, and the relationship between per capita energy consumption and economic growth in Pakistan, and found that there is a two-way causal relationship between them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results show that determinants of electricity consumption function are co integrated and influx of foreign direct investment, income and population growth is positively related to electricity consumption in Pakistan. Ahmed et al (2013) analyzed the link between electricity consumption per capita and real per capita income, over a 34-year period between 1975 and 2009. The study gives evidence of bidirectional causality between energy consumption per capita and per capita revenue on one hand; and power consumption per capita and actual per capita revenue on the other hand.…”
Section: Literature Reviewmentioning
confidence: 99%